Anesthetic considerations in Dravet syndrome. Issue 10 (20th July 2022) - Macdonald‐Laurs, Emma; Corlette, Sebastian; Davidson, Andrew; Howell, Katherine B.
Abstract: We describe a two‐year‐old boy with Dravet syndrome, a severe genetic epilepsy, who developed a generalized tonic–clonic seizure immediately following an intravenous bolus of lidocaine given for propofol pain amelioration during induction of anesthesia for emergency gastroscopy. Although lidocaine has not specifically been reported as potentiating seizures in Dravet syndrome, it is well‐established that sodium channel blockers can worsen seizures in this population.